2015
DOI: 10.1186/s13045-015-0205-6
|View full text |Cite
|
Sign up to set email alerts
|

Redirection of CD4+ and CD8+ T lymphocytes via an anti-CD3 × anti-CD19 bi-specific antibody combined with cytosine arabinoside and the efficient lysis of patient-derived B-ALL cells

Abstract: BackgroundB-acute lymphoblastic leukemia (B-ALL) is derived from B cell progenitors. Recently, the development of appropriate combinations of chemotherapy and immunotherapy represents a promising approach for eliminating cancer. We previously constructed an anti-CD3 × anti-CD19 bi-specific antibody in a diabody configuration and its disulfide-stabilized format (ds-diabody). The combination of the diabody or ds-diabody and Ara-C was highly effective in enhancing the cytotoxicity of T cells against the CD19+ hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 52 publications
(48 reference statements)
2
16
0
Order By: Relevance
“…BsAbs can not only bridge therapeutics (e.g., T cells, drugs) and targets (e.g., tumor) but also simultaneously block two different pathogenic mediators [ 83 ]. In the near future, bsAbs might improve treatment options against cancer, autoimmune diseases, and inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…BsAbs can not only bridge therapeutics (e.g., T cells, drugs) and targets (e.g., tumor) but also simultaneously block two different pathogenic mediators [ 83 ]. In the near future, bsAbs might improve treatment options against cancer, autoimmune diseases, and inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…When we identify a molecule that is highly expressed in cancer and rarely expressed in normal tissues, it is important to know whether there is clinical value to this information. Some researchers have developed an anti-CD19 monoclonal antibody with high killing activity against B cell malignancies, acute lymphoid leukemia, and B-ALL cells based on a specific B cell marker (CD19) [ 34 36 ]. Debra and colleagues found that anti-HuD-based immunotoxin therapy might be an effective alternative treatment for patients with small cell lung cancer and neuroblastoma because the HuD antigen is expressed in 100 % of small cell lung cancer cells and in over 50 % of neuroblastoma cells [ 37 ].…”
Section: Targeted Therapy Researchmentioning
confidence: 99%
“…Until recently, BsAb is intensively investigated [ 9 ]. BsAb can enhance tumor killing in a non-MHC-restricted manner by redirecting effector cells (e.g., T cells, NK cells, macrophages, and monocytes) to the tumor cells [ 10 , 11 ]. Moreover, BsAb not only offers an effective linkage between therapeutics (e.g., immune effector cells, radionuclides) and targets (e.g., tumor cells) but also simultaneously blocks two different oncogenic mediators such as anti-epidermal growth factor receptor (EGFR) × anti-HER2 and anti- EGFR × anti-c-MET [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%